STRATEGI PROGRAM FOOD ESTATE BERBASIS MASYARAKAT DI DESA RIA-RIA KECAMATAN POLLUNG KABUPATEN HUMBANG HASUNDUTAN PROVINSI SUMATERA UTARA - Muhammad Azhar; Ok Hasnanda (Universitas Andi Djemma Palopo, 2022)
Food estate is a food development program in several sectors such as the agricultural, plantation and livestock sectors that are integrated in certain areas. The food estate area can also be categorized as a food barn area. In Indonesia, the establishment of food estates has been started since 2020, namely in the provinces of Central Kalimantan and North Sumatra as the largest food estate development area, which is approximately 30,000 hectares. In particular, in the province of North Sumatra, a food estate area will be established with horticultural commodities as its focus. The perpose of this study is to analys the internal and external factors that affect the food estate programe, analize alternatife strategy that can be done and identify the priority strategy in the development of the food estate program that’s conducted in Ria-Ria Village, Pollung District, Humbang Hasundutan Regency, North Sumatra Province.This study uses descriptive quantitative methods (interviews, participant observation, literature study) and data analysis using SWOT analysis (strengths, weaknesses, opportunities, threats). The results showed that the Internal Factors (IFAS) and External Factors (EFAS) in the Food Estate Program obtained the highest scores were Strengths and Opportunities (SO) followed by ST, WO, and WT. The weight x rating generated by the Food Esatte Program on strength (S) is 2.56, Weakness (W) is 1.34, opportunity is 0.92, and threat (T) is 0.67. By analyzing alternative strategies by collaborating with Balitbang and universities, improving the quality and government attention to farmers in the food barn area, creating innovations and improving the quality of fertilizers used and requiring improvement efforts used to maintain the productivity of the food estate. The position of the Food Estate Program in strategic environmental analysis (internal and external environment) is in quadrant one (I) or in an aggressive position that supports the food estate strategy program, namely the SO strategy (aggressive strategy).